2020
DOI: 10.5194/acp-20-6243-2020
|View full text |Cite
|
Sign up to set email alerts
|

Seawater analysis by ambient mass-spectrometry-based seaomics

Abstract: Abstract. An analytical method coupled to multivariate statistical analysis was developed based on transmission-mode direct analysis in real-time quadrupole time-of-flight mass spectrometry (TM-DART-QTOF-MS) to interrogate lipophilic compounds in seawater samples without the need for desalinization. An untargeted metabolomics approach is addressed here as seaomics and was successfully implemented to discriminate the sea surface microlayer (SML) from the underlying water (ULW) samples (n=22, 10 paired samples) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…These comparisons demonstrate that the majority of the results and features detected by both tools are in agreement, and that Tidy-Directto-MS correctly processed the DART-MS data set. The Tidy-Direct-to-MS pipeline was also able to detect the discriminant features reported by Zabalegui et al 17 Furthermore, an interbatch drift correction (see Batch Correction section) was performed after feature detection and processing with the Tidy-Direct-to-MS pipeline. A time dependent intensity drift was successfully corrected using the pooled QC samples, yielding mean abundance shift factors of between 0.75 and 1.32 across the acquisition batches.…”
Section: Semiautomated Parameter Optimizationmentioning
confidence: 97%
See 3 more Smart Citations
“…These comparisons demonstrate that the majority of the results and features detected by both tools are in agreement, and that Tidy-Directto-MS correctly processed the DART-MS data set. The Tidy-Direct-to-MS pipeline was also able to detect the discriminant features reported by Zabalegui et al 17 Furthermore, an interbatch drift correction (see Batch Correction section) was performed after feature detection and processing with the Tidy-Direct-to-MS pipeline. A time dependent intensity drift was successfully corrected using the pooled QC samples, yielding mean abundance shift factors of between 0.75 and 1.32 across the acquisition batches.…”
Section: Semiautomated Parameter Optimizationmentioning
confidence: 97%
“…The seaomics data set from Zabalegui et al 17 was processed with the developed pipeline, to showcase the capabilities of the tool. While this work focused on how to apply the tool in a particular experiment, the proposed framework is still general for other direct-to-MS-based metabolomics studies.…”
Section: Semiautomated Parameter Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, analysis of PFAS is performed utilizing LC-MS/MS techniques. , While these methods are highly sensitive and allow effective separation of isomeric species and quantification, alternative techniques such as direct ambient mass spectrometry (AMS) can enable higher sample throughput, which is ideal for screening purposes . The plasma-based AMS technique direct analysis in real time (DART) enables high throughput screening and quantification of various classes of molecules for both positively and negatively ionized species. Furthermore, there has been recent interest in the DART analysis of PFAS, with results from Cody and Maleknia demonstrating robust ng/L level quantification of PFOA and the screening of various other PFAS such as PFOS, using coated glass capillaries (CGCs) with octadecylamine as an extraction phase for PFAS . In fact, many developed AMS methods benefit from analyte preconcentration prior to instrumental analysis. , Previous work from our research group has demonstrated the use of solid phase microextraction (SPME) devices composed of hydrophilic–lipophilic balance–weak anion exchange particles embedded in polyacrylonitrile (HLB-WAX/PAN) as an ideal strategy for the preconcentration of multiple classes of PFAS, allowing sub-ng/L detection when coupled with LC-MS/MS. , …”
Section: Introductionmentioning
confidence: 99%